The poisoning effect of KCl and K2O on CeO2-TiO2 catalyst for selective catalytic reduction of NO with NH3. (15th November 2020) - Jiang, Ye; Lai, Chengzhen; Li, Qingyi; Gao, Wenqian; Yang, Lin; Yang, Zhengda; Lin, Riyi; Wang, Xinwei; Zhu, Xinbo
Graphical abstract: Highlights: K2 O deactivated Ce-Ti oxide catalyst more seriously than KCl at the same K loading. Fewer Ce 3+ and chemical adsorbed oxygen on the surface of K2 O-CT. Lower surface acidity and worse reducibility over K2 O-CT. K species inhibited the adsorption of NH3 and promoted the formation of NO x . Abstract: Based on experiments and DFT studies, CeO2 -TiO2 catalyst was found to be deactivated by KCl or K2 O, and the poisoning effect of K2 O was more serious than that of KCl. The characterization results showed that compared with KCl, K2 O could lead to a greater decrease in surface acidity, reducibility, the ratio of Ce 3+ /Ce 4+ and the concentration of the chemisorbed oxygen on the surface of CeO2 -TiO2 catalyst. The results of in situ DRIFT showed that K2 O had a stronger inhibition effect on NH3 adsorption on the catalyst surface than KCl. The introduction of K2 O or KCl promoted the adsorption of NO on the catalyst surface, but not all NO x adspecies were reactive in the NH3 -SCR reaction. These results were further demonstrated by DFT calculations. The PDOS of different K species doped CeO2 -TiO2 catalysts and the adsorption energies of oxygen vacancy, chemisorption oxygen, NH3 and NO x were calculated by MS DMol3. It was found that the introduction of K species weakened the reactivity of the catalyst surface, inhibited the formation of oxygen vacancies and chemisorption oxygen, and reduced the adsorption of NH3 on the catalyst surface, all of which led to the decrease in the catalytic activity.